The Role of Transcription Factor 21 in Epicardial Cell Differentiation and the Development of Coronary Heart Disease - Hu, Haochang; Lin, Shaoyi; Wang, Shuangshuang; Chen, Xiaomin (Frontiers in Cell and Developmental Biology, 2020)
Transcription factor 21 (TCF21) is specific for mesoderm and is expressed in the embryos’ mesenchymal derived tissues, such as the epicardium. It plays a vital role in regulating cell differentiation and cell fate specificity through epithelial-mesenchymal transformation during cardiac development. For instance, TCF21 could promote cardiac fibroblast development and inhibit vascular smooth muscle cells (VSMCs) differentiation of epicardial cells. Recent large-scale genome-wide association studies have identified a mass of loci associated with coronary heart disease (CHD). There is mounting evidence that TCF21 polymorphism might confer genetic susceptibility to CHD. However, the molecular mechanisms of TCF21 in heart development and CHD remain fundamentally problematic. In this review, we are committed to providing a detailed introduction of the biological roles of TCF21 in epicardial fate determination and the development of CHD.